AUTHORITARIAN THIRD WAY IN THE ERA OF FASCISM ([S.l.])
1 online resource
Keywords: This book takes a transnational and comparative approach that analyses the process of diffusion of a third way in selected transitions to authoritarianism in Europe and Latin America. When looking at the authoritarian wave of the 1930s, it is not difficult to see how some regimes appeared to offer an authoritarian third way somewhere between democracy and fascism. It is in this context that some Iberian dictatorships, such as those of Primo de Rivera in Spain, Salazar's New State in Portugal and the short-lived Dollfuss regime in Austria are mentioned frequently. Especially during the 1930s, and in those parts of Europe under Axis control, these models were discussed and often adopted by several dictatorships. This book considers how and why these dictatorships on the periphery of Europe, especially Salazar's New State in Portugal, inspired some of these regimes' new political institutions particularly within Europe and Latin America. It pays special attention to how, as they proposed and pursued these authoritarian reforms, these domestic political actors also looked at these institutional models as suitable for their own countries. The volume is ideal for students and scholars of comparative fascism, authoritarian regimes, and European and Latin American modern history and politics.